A comparably high virulence strain of porcine reproductive and respiratory syndrome virus isolated in Taiwan. (August 2019) - Hou, Fu-Hsiang; Chia, Min-Yuan; Lee, Yi-Han; Liao, Jiunn-Wang; Lee, Wei-Cheng
Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) has been endemic in Taiwan since 1991. This study aimed to present a highly virulent PRRSV in Taiwan based on farm data collection and both in vitro and in vivo evaluations in virus challenge studies. This virulent PRRSV strain was first noticed on Farm TSYM due to continuously high nursery mortality rate and severe PRRSV-associated pneumonia. In phylogenetic surveillance, the PRRSV TSYM-strain remained in the predominant position for years, even with several other PRRSV strain invasions. In laboratory challenge trials, the TSYM-strain led to prolonged pyrexia, growth retardation, high mortality rates and high viremia titer that similar to the highly pathogenic PRRSV. The TSYM-strain isolate also triggered early interleukin-10 up-regulation and significantly higher infection rates under in vitro experiments. This study provides information of a comparably virulent strain in Taiwan and its appearance in both farm and laboratory levels.